UPAYA OPTIMALISASI POTENSI DESA CIBULUH MELALUI KEGIATAN PENGABDIAN - Amelia Limijaya, Dkk (Universitas Muhammadiyah Sumatera Utara, 2017)
The devotion activities undertaken in Cibuluh Village is one of the efforts to support the Nawa Cita program proclaimed by the government, especially the 3rd and 5th points, which is about building Indonesia from the periphery by strengthening the regions and villages within the framework of the unitary state and improving quality of life of Indonesians through the improvement of the quality of education and training, and in line with UNPAR's vision to